M'S SELF-ACTUALIZATION JOURNEY IN 'HOW TO MAKE MILLIONS BEFORE GRANDMA DIES' (2024) - Roselyn, Elvitra (ELite Journal : International Journal of Education, Language and Literature, 2026)
How to Make Millions Before Grandma Dies (2024) is a Thai film that depicts a young man's journey toward self-actualization amid complex family conflicts. This study analyzes how M's self-actualization shows and the influence of other family members in this process. Applying Abraham Maslow's concept of self-actualization, adapted by Kaufman into the Characteristic of Self-Actualization Scale (CSAS), this study explores M's characteristic development through content analysis, utilizing dialogue and visual elements to reveal the family's influence on M's growth. Findings highlight the vital role of each character as a catalyst and barrier of family Influence factors (including financial and informational support, expectations, and values or beliefs) in triggering M's characteristics, such as acceptance, authenticity, purpose, humanitarianism, and efficient perception of reality. This study concludes that family influence significantly impacts an individual's self-actualization and emotional maturity journey.